Irradiation-induced formation of nanorod precipitates in a dilute Cu–W alloy. (1st April 2016) - Shu, Shipeng; Zhang, Xuan; Beach, John A.; Bellon, Pascal; Averback, Robert S.
Abstract: Radiation-enhanced precipitation of W has been investigated in dilute Cu-W alloys. While spherical W precipitates are stabilized during irradiation below 300 °C and above 600 °C, irradiation at 500 °C results in the formation of nanorods. Furthermore, use of two-step irradiations, first one at 600 °C followed by one at 500 °C, indicates that the morphological transformation is reversible. The stabilization of W nanorods is rationalized using a model introduced by Frost and Russell to explain size stabilization of precipitates formed during irradiation, but extended here to consider precipitate morphology. Graphical abstract: